St Patrick and St Maughold: Saints' Dedications in the Isle of Man - (:unkn) unknown (My University, 2016)
Centrally located in the Irish Sea, the Isle of Man possesses a rich cultural heritage. In many ways uniquely Manx, it is nevertheless clearly related to Mann’s place as a cultural crossroads. The long-term dynamics of Manx culture are reflected in its saints’ dedications: the evidence of the dedications themselves, the medieval dedication sites and their successors, and the communities, past and present, associated with those sites. Of particular interest are the medieval ecclesiastical sites with dedications to Patrick, Apostle of the Irish. The Patrician evidence is compared to that for Maughold, a second saint significant in the Isle of Man.
Keywords: Saint Patrick; Saint Maughold; saints’ dedications; Manx folklore; Isle of Man; cultural heritage